Efektifitas Pemberian Minyak Zaitun Ekstra Virgin Terhadap Kadar Glukosa Darah Tikus Wistar Jantan Dengan Induksi Hiperglikemia - Sri Lestari Dwi Astuti; Yeni Tutu Rohimah (Poltekkes Kemenkes Surakarta, 2018)
Background: The global population of diabetes mellitus tends to increase every year. This is related to the increased of population numbers, lifestyle, increased prevalence of obesity and less physical activity (Smeltzer & Bare, 2002). Olive oil is a functional diet because it is rich of monounsaturated fatty acids (MUFA), especially oleic acid (70% - 80%), contains antioxidants and polyphenol compounds. Polyphenols are α-amylase enzyme inhibitors that have function in the breakdown of carbohydrates, so that the level of blood glucose in hyperglycemia can be lowered (Astrawan made, Wresdiyati Tutik, Nasution Nurlayla Amas, 2015). The goal of this study is to examine the effectiveness of extra virgin olive oil to blood glucose level. Method:This study used experimental laboratory study with post test only control group design. The independent variable was the extra virgin olive oil, while the dependent variable was the blood glucose level. The samples were 32 healthy 8 weeks old white male wistar strain rats with the weigh between 180 mg - 200 mg. It divided into 3 groups, the negative control group was fed with standard diet, the positive control group was fed with standard diet and 1 ml fructose for 4 weeks, the treatment group was fed with standard diet, 1 ml fructose and 0.5 gr extra virgin olive oil for 4 weeks, on the fifth week the fructose was increased into 4 ml/day for the next 4 weeks, on the 52nd day the blood glucose level was checked after it was fasted for 6 hours. The data analysis used t-test and Mann Withney test with α = 0.05. Result: The blood glucose level average of the positive control group was 309.57 ± 120.12, the blood glucose level average of the negative control group was 111.85 ± 10.57, the blood glucose level average of the treatment group was 115.12 ± 12.25. Conclusion: Giving the extra virgin olive oil can effectively lower the blood glucose level on the male wistar rats.